Ukuran mesiodistal dan servikoinsisal gigi insisivus sentralis suku Bugis, Makassar, dan Toraja tidak menunjukkan perbedaan yang bermakna Size of mesiodistal and cervicoincisal maxillary central incisors between Buginese, Makassarese, and Torajanese showed no significant difference - Irene Edith Rieuwpassa; Nurlindah Hamrun; Fitrian Riksavianti (Journal of Dentomaxillofacial Science, 2013)
Every tribe and race has size of tooth mesiodistal and cervicoincisal different from each other. The most obviousdifference is the size of the teeth between female and male. This study aimed to determine differences in size ofmesiodistal and cervicoincisal maxillary central incisors between male and female of Buginese, Makassarese andTorajanese. The sample consisted of 30 Buginese, 30 Makassarese, and 30 Torajanese aged frem 18-25 years-old.After impression of the upper and lower jaw was taken, and size of mesiodistal and cervicoincisal tooth weremeasured. After the data were analyzed by t-test and ANOVA test, it appears that males have a larger size thanfemales. Makassarese has the longest mesiodistal size (8.41 mm), Buginese has the longest cervicoincisal size (9.83mm), whereas Torajanese has the smallest size of mesiodistal and cervicoincisal among the other tribes. It was concluded that the average sizes of mesiodistal and cervicoincisal of maxillary central incisors showed no significantdifference. While there are significant differences in the average size of the mesiodistal and cervicoincisal maxillarycentral incisors between the males and females, and based on tribe lines.